La nouvelle loi canadienne sur les sociétés d’assurances et les droits politiques des assurés - Gingras, Claude (Assurances, 1992)
The new federal insurance legislation, which received his Royal Assent last December, and is expected to come into force this spring, will replace the Canadian Insurance and British Insurance Companies Act and the Foreign Insurance Companies Act. The author, Claude Gingras, analyzes the new set of rules contained in the new legislation governing the political rights of policyholders such as the right to receive notice of a meeting of shareholders, the vote by means of a proxy and the right to submit proposals. Mr. Gingras comes to the conclusion that such political rights seem to be privileges, are not equivalent to those of shareholders and contain significant loopholes.